(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
In this study, the possibility of purifying industrial wastewater from the “Electrochemical Plant” JSC was investigated using sorbents prepared from thermally treated opoka mineral and Ailanthus tree biomass. The experimental results showed that increasing the amount of Ailanthus-based sorbent significantly enhanced the removal efficiency of heavy metal ions (Cu²⁺, Ni²⁺, Zn²⁺, Sr²⁺, Se²⁻, Al³⁺), reaching 85–95%, while the total mineralization of the wastewater decreased by 30–35%. The highest purification efficiency was achieved when a mixture containing 0.8% thermally activated opoka and 0.2% Ailanthus sorbent was applied.